Neuro-Inspired Quantization - Doutsi, Effrosyni; Fillatre, Lionel; Antonini, Marc; Gaulmin, Julien (Proceedings - International Conference on Image Processing, 2018)
This paper presents a novel neuro-inspired quantization model which is the extension of the recently released perfect-Leaky Integrate and Fire (LIF) model. We propose that the LIF, which is a very efficient neuromathematical model that describes the spike generation neural mechanism, can lead to a groundbreaking and above all dynamic compression algorithm which is called LIF encoder/decoder. We also prove that under some assumptions, there is a link between the novel LIF encoder/decoder and the conventional Uniform Deadzone Quantizer (UDQ).